Use of 5E Learning-cycle and Concept-mapping Strategies for Improving Student's Performance in Genetics in Secondary Schools in Kwara State, Nigeria - Jibril, Basira Abdulrahim (Pascasarjana, Mataram University, 2024)
The continuous explosion of discoveries in field of science and technology in this 21st century calls for shift from conventional teaching methods to a more innovative teaching strategies in Nigerian secondary schools. Instructional strategies adopted by teachers have been linked by researchers to students’ conceptions, misconceptions, difficulties of some concepts as well as poor performances in science subject like Biology at the senior school certificate examinations in Nigeria. Genetics is one of the concepts in Biology that was reported by researchers to be difficult to teach by teachers and difficult to learn by students in secondary schools in Nigeria. This study examined the effect of using 5E learning-cycle and concept-mapping in teaching genetics to senior school students offering biology. The study is a quasi-experimental type. Sample comprised of senior school two students in public secondary schools in Ilorin city. The study is a quasi-experimental type involving pretest, posttest, non- randomized and non-equivalent control groups. All Senior School two (SS II) Biology students were the targeted population. The target population will not be preparing for WASSCE. A purposive sampling technique was used to select co-educational government secondary schools in three senatorial districts. A Performance Test on Genetics (PTG) was used for data collection. Data collected were analyzed using mean and ANCOVA statistical tool. The study revealed that both learning-cycle and concept- mapping had a positive effect on the performance of the experimental groups. It means there is a significant difference between the experimental and control groups and also, no significant difference between the performance of male and female students. It was therefore recommended among others that teachers should employ these strategies to teach biology particularly genetics